Maxillary Reconstruction Timing in Severe Systemic Lupus Erythematous (SLE) Patient with Bone Destruction due to Invasive Aspergillosis: Case Report - Yulyani Werdhiningsih; Ayu Paramaiswari; Deddy Nur Wachid Achadiono; Nyoman Kertia (Acta Interna The Journal of Internal Medicine, 2020)
Severe Systemic Lupus Erythematosus patient was in the third of 28-days-cycle cyclophosphamide chemotherapy when the early symptoms of aspergillus infection occurred. This developed into extensive cranial bone damage. It was planned to get a biopsy and debridement for bone and soft tissue to diagnose and therapy palate osteonecrosis, followed by reconstruction surgery. This case report aimed to report the successful management of a severe patient on chemotherapy undergoing several operations so that the SLE aspergillosis is optimally managed.